2013
DOI: 10.1007/s12630-013-9932-8
|View full text |Cite
|
Sign up to set email alerts
|

Residual paralysis: a real problem or did we invent a new disease?

Abstract: Purpose Over the past three decades, many studies have shown a high proportion of patients in the recovery room with residual neuromuscular blockade after anesthesia. The purpose of this Continuing Professional Development module is to present the physiological consequences of residual paralysis, estimate the extent of the problem, and suggest solutions to prevent its occurrence. Principal findings Residual paralysis is defined as a train-of-four ratio (TOFR) \ 0.9 at the adductor pollicis. While tidal volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 36 publications
0
35
0
14
Order By: Relevance
“…The median (IQR [range]) times from administration of the reversal agents to a TOF ratio of 0.9 in the TOF4, TOF-fade and DBS-fade groups was 11 (9-15.5 ) min, 8 (4-13.5 ) min and 7 (4-10 [2][3][4][5][6][7][8][9][10][11][12][13][14][15]) min, respectively. The reversal time to a TOF ratio of 0.7 and 0.8 was shorter in the TOF-fade and DBS-fade groups than in the TOF4 group (p = 0.001 and 0.0013, respectively) and the time to a TOF ratio of 0.9 was shorter in the DBS-fade group than in the TOF4 group (p = 0.046) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The median (IQR [range]) times from administration of the reversal agents to a TOF ratio of 0.9 in the TOF4, TOF-fade and DBS-fade groups was 11 (9-15.5 ) min, 8 (4-13.5 ) min and 7 (4-10 [2][3][4][5][6][7][8][9][10][11][12][13][14][15]) min, respectively. The reversal time to a TOF ratio of 0.7 and 0.8 was shorter in the TOF-fade and DBS-fade groups than in the TOF4 group (p = 0.001 and 0.0013, respectively) and the time to a TOF ratio of 0.9 was shorter in the DBS-fade group than in the TOF4 group (p = 0.046) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A TOF ratio >0.9 is attained in 2–3 min when appropriate doses are given. [4] In our study, we were using continuous NMT monitoring which displayed TOF ratio and PTC. NMT monitoring is essential to determine the proper dose of SUG.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in patients with a more intense residual block (train-of-four count 1-3), even a dose of 70 mcg/kg was not found to be effective in producing an adequate reversal (defined as a TOFR >0.9) 10 min after application in 75-100% of the included patients [36]. It has been suggested that in these patients, the agent may improve the early recovery but possibly delay the later one, which finally results in an unsatisfying efficacy [37]. Consequently, it has been recommended that neostigmine for reversal should be only administered if recovery progress has reached at least four responses following a train-of-four stimulation [38].…”
Section: Reversal With Neostigminementioning
confidence: 96%